2022
DOI: 10.1186/s12987-022-00345-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of brain iron uptake by apo- and holo-transferrin is dependent on sex and delivery protein

Abstract: Background The brain requires iron for a number of processes, including energy production. Inadequate or excessive amounts of iron can be detrimental and lead to a number of neurological disorders. As such, regulation of brain iron uptake is required for proper functioning. Understanding both the movement of iron into the brain and how this process is regulated is crucial to both address dysfunctions with brain iron uptake in disease and successfully use the transferrin receptor uptake system f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…The constant utilization of iron for metabolic processes likely leads to an increased requirement of iron uptake into the brain. Our in vivo study supports this, where we found that, within 24 hours, brain iron uptake increased with apo‐Tf infusions in males but not in females (Baringer et al, 2022), potentially because the iron uptake signaling (apo‐Tf) in females was already maximally elevated.…”
Section: Regulation In Homeostasissupporting
confidence: 88%
See 3 more Smart Citations
“…The constant utilization of iron for metabolic processes likely leads to an increased requirement of iron uptake into the brain. Our in vivo study supports this, where we found that, within 24 hours, brain iron uptake increased with apo‐Tf infusions in males but not in females (Baringer et al, 2022), potentially because the iron uptake signaling (apo‐Tf) in females was already maximally elevated.…”
Section: Regulation In Homeostasissupporting
confidence: 88%
“…Indeed, Chiou et al reported that FTH1 is released as an iron delivery protein for ECs (Chiou et al, 2019) and showed that basal apo‐ and holo‐Tf affected the amount of FTH1‐bound iron that was transported across the ECs in a similar manner as Tf‐delivered iron (Chiou et al, 2019). However, our in vivo study found no change in FTH1 uptake when the levels of apo‐ and holo‐Tf were manipulated via intraventricular infusion (Baringer et al, 2022). The differences between the results of these two studies are likely due to the complex dynamics of iron uptake in vivo including differences in signaling that regulates uptake of Tf and FTH1.…”
Section: Regulation In Homeostasismentioning
confidence: 77%
See 2 more Smart Citations
“…Tf-bound iron is taken up via transferrin receptor (TfR) expressed on the luminal side of the blood–brain barrier endothelial cells (BBBECs), which leads to receptor-mediated endocytosis ( 8 , 9 ), and studies have shown receptor-mediated transcytosis of Tf-bound iron directly from the luminal side of the BBBECs to the brain ( 10 , 11 ). We have established that H-ferritin (FTH1) can also transport iron to the brain both in vitro and in vivo ( 12 , 13 ). Ferritin is an iron storage protein capable of binding 4500 iron atoms, that is made up of two subunits: FTH1 and L-ferritin ( 14 , 15 ).…”
mentioning
confidence: 99%